Community Empowerment Strategy Based on Social Capital in Supporting Accelerated Mangrove Rehabilitation (Case Study in Kateman District, Indragiri Hilir Regency, Riau Province) - Ramadona, Tomi; Darwis, Darwis; Nugroho, Firman; Wildah, Sri Wahyuni; Septya, Fanny (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2024)
Kateman District in Indragiri Hilir Regency, Riau Province, is known for its extensive mangrove forests. However, ongoing damage and coastal erosion have led to significant deforestation. This study examines the socio-economic characteristics and social capital of communities near mangrove areas to create empowerment strategies for mangrove rehabilitation. Data was collected using PRA methods, observation, in-depth interviews, and literature review, and analyzed qualitatively and quantitatively. Findings reveal strong community support for the rehabilitation program, with local social capital playing a key role in these efforts. In Kateman District’s coastal communities, key social capital elements include (a) awareness and responsibility, (b) groups and networks, (c) trust and solidarity, (d) collective and cooperative actions, (e) information and communication, and (f) cohesion and inclusion. Community empowerment strategies are designed based on these social capital factors. Based on the AHP results, five alternative priority strategies need to be developed, namely: 1) bottom-up approach (0.155); 2) institutional strengthening (0.136); 3) training and capacitation (0.130); 4) Pentahelix collaboration (0.130); and 5) participatory monitoring and evaluation (0.123). The analysis suggests that to support mangrove rehabilitation, local governments and agencies should strengthen institutions through regional or village regulations and build partnerships with stakeholders, leveraging local social capital.